A Quality Estimator of Acoustic Sounding Detection - Lurton, Xavier; Ladroit, Yoann; Augustin, Jean-Marie (The International Hydrographic Review, 2010)
Swath sonar bathymetry accuracy depends on the intrinsic performance of acoustic signal processing. We propose here a quality factor, quantifying the accuracy associated with every sounding computation. This descriptor is derived from simple models either for amplitude (variance of the centre-of-gravity instant of a fluctuating bell-shaped envelope) or for interferometric phase (local variance for a number of processed samples). The purpose is to attach to each individual sounding an objective quality level that is sonar independent, and directly applicable in bathymetry processing, either in data editing, or as an input parameter to statistical post-processing. This concept is illustrated by examples from experimental data.